Stereoelectronic Control in Diels−Alder Reaction of Dissymmetric 1,3-Dienes - Mehta, Goverdhan; Uma, R (Accounts of chemical research, 2000)
The Diels−Alder reaction is a widely employed protocol in which four stereogenic centers are generated in a predictable manner with olefin geometry, adjoining chiral center, and transition-state topology serving as the main controlling elements. However, when the Diels−Alder partners are in a dissymmetric environment, π-face selection is determined through the interplay of steric, orbital, and electrostatic factors whose relative importance is a subject of intense debate. Several new systems have been crafted to probe the mechanistic nuances of the π-face selection. The available data have enabled us to qualitatively define a hierarchy of various stereoelectronic effects that would aid predictability of the stereochemical outcome.